PENGARUH KONFLIK PERAN GANDA DAN KETERAMPILAN TERHADAP PRODUKTIVITAS PADA PT ROYAL KORINDAH (Studi Kasus pada Karyawan Bagian Produksi) - Evy Paramytha; Ari Pradhanawati (Universitas Diponegoro, 2020)
Labor productivity is an important thing that must be considered and often used to measure the extent to which workers can reach the target set company. Labor productivity can be influenced by several factors among them are dual role conflicts and skills. PT Royal Korindah Purbalingga is an industrial company that develops with the production and export of false eyelashes. The purpose of this research is to know the influence of the dual role conflict and skills against labor productivity on PT Royal Korindah Purbalingga. This research using a quantitative approach. Sample 90 laborers several women who are married and have a child using a probability sampling technique. Data collection use instruments in the questionnaire. Analysis research on the SPSS20.0 version. The result showed that the dual role conflict influences productivity with count -5,906 > t table 1,9873. Skills influences productivity with t count 8,727 > t table 1,9873. Simultaneously the dual role conflicts and skills influence productivity with an f count 53,998 & gt; f table 3,101 with the significance 0,000 >0,05. The suggestions for this research is to support the dual role of workers women and increase their skills by providing training. These two variables have some indicators that are not optimal to be able to increase productivity can be done by reducing dual role conflicts and increasing skills